Staff perspectives on supporting individuals with eating disorders—a qualitative analysis of approaches and methods - Maja Jepsen; Nanna Kaas Tepavicharov; Line Nørgaard Remmen; Julie Katrine Karstensen; Jeanette Reffstrup Christensen (Cogent Psychology)
This phenomenological-hermeneutical qualitative study explored the perspectives of 12 staff members at a residential facility in Denmark on the approaches and methods used to support individuals with eating disorders. Data were analysed using a qualitative content analysis framework. The primary benefit reported by participants was the ability to view individuals beyond their diagnoses, addressing underlying issues rather than solely focusing on physical symptoms. Participants also emphasized the significance of a compassionate and empathetic approach in fostering a supportive environment conducive to recovery. The study revealed new insights into improving quality of life and establishing constructive behavioural patterns through the bio-psycho-social model and metacognitive approaches derived from metacognitive therapy. The residential facility’s holistic and individualized methods are positively received by staff, who find them valuable and meaningful for supporting individuals with eating disorders. The staff believe these methods are crucial for recovery and improving quality of life. Future research could further explore the long-term impacts of such approaches on recovery outcomes.